Farming cattle in the tropics: Transnational science and industrializing pastures in Brazil - Nehring, Ryan (Wiley, 2024)
Societal Impact Statement Society is increasingly concerned over the environmental impact of diets. Much of this concern is over the environmentally destructive nature of meat production, especially beef and especially in the Amazon. This article aims to understand the production of beef in Brazil through the understudied perspective of forage grasses. In doing so, the article traces who was involved in the importation and improvement of forage grasses in Brazil, why they were involved, and what the consequences of their actions were. By centering forage grasses, we can better understand the potential consequences of seemingly unimportant plant breeding efforts.